O uso da robótica pedagógica em três escolas municipais de Belo Horizonte - Quézia Andrade da Conceição (2020)
Pedagogical Robotics (PR) has been the target of actions by the Belo Horizonte Municipal Education Secretariat (SMED) for educational practices in elementary education since 2018. It was observed from an initial investigation on the website of the Coordination for the Improvement of Higher Education Personnel (CAPES) that scientific studies on this type of Educational Technology have been developed in colleges in non-educational areas. There is also a lack of studies on PR in the years prior to elementary school and on PR practices in municipal schools in Belo Horizonte that already have projects for their use. This research was developed at UFMG's professional master's degree, PROMESTRE and sought to understand the potential use of Pedagogical Robotics in three public schools of Municipal Education Network of Belo Horizonte (RMEBH). To achieve this goal, this research was developed in an explanatory case study of the qualitative nature. Regarding the field research, questionnaires and interviews were applied and the practice of PR was observed in one of the schools. An informative and experimental website on Pedagogical Robotics was also developed, with reflections and didactic notes to encourage and mediate the work of documents. The results demonstrated that PR has potential in both curricular areas and social aspects. It was also found that the projects of the schools surveyed happen much more by groups of the school group itself than by SMED actions. However, we realize that these actions are also quite important, especially for schools that are unfamiliar, and that a PR is not unique to a specific cycle or area, as teachers of various disciplines and cycles are responsible for projects, which It also highlights its multidisciplinary and interdisciplinary role. Thus, it is expected to contribute conceptually to reflections and practices involving Pedagogical Robotics in the school space.